EFFECTS OF PHYSICAL EXERCISE ON HEART RATE VARIABILITY IN POSTMENOPAUSAL WOMEN: A SYSTEMATIC REVIEW WITH META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - Wang, Xinyu; Jie, Yi; Yu, Hui; Guo, Yongkun; Dong, Anqin (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Background: Heart rate variability is a marker of the cardiac autonomic system and is associated with the mortality of cardiovascular disease. Decreased physical exercise may induce a lower level of heart rate variability and poor cardiac function in postmenopausal women. This review aimed to address the relationships between physical exercise and heart rate variability and to provide clinical evidence for the formulation of exercise prescriptions for improving cardiovascular function in postmenopausal women. Method: Authors searched 5 databases including PubMed, Scopus, Embase, Cochrane Library, and Web of Science to identify eligible articles between database inception and May 13, 2023. All randomized controlled trials of exercise intervention for postmenopausal women were included, only English articles and without date restrictions. The standardized mean differences of heart rate variability time domain parameters and frequency domain parameters were calculated, comparing postmenopausal women who did and who did not exercise via random-effects meta-analyses. The quality of the evidence was assessed with the Cochrane risk of bias tool. This study was registered on PROSPERO, number CRD42020208037.